The Impact of Fundamentalist Terrorism on School Enrolment: Evidence from North-Western Pakistan, 2004-09 - Sarah Khan; Andrew Seltzer (Institute for the Study of Labor (IZA), 2016)
Islamist groups in Afghanistan, Pakistan, and elsewhere have sought to remove females from public life. This paper uses data from Pakistan Social and Living Standards Measurement and the Global Terrorism Database to examine the impact of the Pakistani Taliban's terror campaign in the north-western province of Khyber Pukhtoonkhwa aimed at removing girls from school from the age of 10. Using a difference-in-difference-indifference approach, we show that low levels of exposure to terrorism had little effect on school enrolment. High levels of exposure reduced the enrolment rate for boys by about 5.5 percent and girls by about 10.5 percent. This decline in enrolment, although strongly significant, is far smaller than has commonly been portrayed in the media. Finally, although the Taliban warned students to enrol in madrassas rather than secular schools, we find no evidence that this led to increased madrassa enrolment in the affected regions.
Keywords: O15; I25; D74; O53; 330; education; terrorism; Pakistan